The papal monarchy : the Western church from 1050 to 1250 - Morris, Colin, 1928- (Oxford history of the Christian Church., 1989)
Traces the influence and legacy of the Roman Catholic Church across two centuries (1050-1250 AD). The text describes folklore and church architecture as well as the Crusades, the Inquisition, papal government, the College of Cardinals, the confessional, chivalry, hospitals and marriage.